Pregnancy Termination and Postnatal Major Congenital Heart Defect Prevalence After Introduction of Prenatal Cardiac Screening - Tomek, Viktor; Jicínská, Hana; Pavlícek, Jan; Kovanda, Jan; Jehlicka, Petr; Klásková, Eva; Mrázek, Jirí; Cutka, David; Smetanová, Dagmar; Brešták, Miroslav; Vlašín, Pavel; Pavlíková, Markéta; et al. (JAMA network open, 2023)
IMPORTANCE: Prenatal cardiac screening of the first and second trimesters has had a major impact on postnatal prevalence of congenital heart defects (CHDs), rates of termination of pregnancy (TOP), and outcomes among children born alive with CHDs. OBJECTIVE: To examine the prenatal and postnatal incidence of major CHDs (ie, necessitating intervention within the first year of life), detection rate trends, rates of TOP, and the association of cardiac screening with postnatal outcomes. DESIGN, SETTINGS, AND PARTICIPANTS: In this cross-sectional study, 3827 fetuses with antenatally diagnosed major CHDs in the Czech Republic (population 10.7 million) between 1991 and 2021 were prospectively evaluated with known outcomes and associated comorbidities. Prenatal and postnatal prevalence of CHD in an unselected population was assessed by comparison with a retrospective analysis of all children born alive with major CHDs in the same period (5454 children), using national data registry. Data analysis was conducted from January 1991 to December 2021. MAIN OUTCOMES AND MEASURES: Prenatal detection and postnatal prevalence of major CHDs and rate of TOPs in a setting with a centralized health care system over 31 years. RESULTS: A total of 3 300 068 children were born alive during the study period. Major CHD was diagnosed in 3827 fetuses, of whom 1646 (43.0%) were born, 2069 (54.1%) resulted in TOP, and 112 (2.9%) died prenatally. The prenatal detection rate increased from 6.2% in 1991 to 82.8% in 2021 (P < .001). Termination of pregnancy decreased from 70% in 1991 to 43% (P < .001) in 2021. Of 627 fetuses diagnosed in the first trimester (introduced in 2007), 460 were terminated (73.3%). Since 2007, of 2066 fetuses diagnosed in the second trimester, 880 (42.6%) were terminated, resulting in an odds ratio of 3.6 (95% CI, 2.8-4.6; P < .001) for TOP in the first trimester compared with the second trimester. Postnatal prevalence of major CHDs declined from 0.21% to 0.14% (P < .001). The total incidence (combining prenatal detection of terminated fetuses with postnatal prevalence) of major CHD remained at 0.23% during the study period. CONCLUSIONS AND RELEVANCE: In this cross-sectional study, the total incidence of major CHD did not change significantly during the 31-year study period. The prenatal detection of major CHD approached 83% in the current era. Postnatal prevalence of major CHD decreased significantly due to early TOPs and intrauterine deaths. The introduction of first trimester screening resulted in a higher termination rate in the first trimester but did not revert the overall decreasing trend of termination for CHDs in general.
Keywords: Prevalence; průřezové studie; Child; indukovaný potrat; Pregnancy; Cross-Sectional Studies; těhotenství; Heart Defects, Congenital; Abortion, Induced; dítě; prevalence; vrozené srdeční vady; Retrospective Studies; retrospektivní studie; lidé; Female; ženské pohlaví; Humans